Introduction to Operations and Supply Chain Management - Bozarth, Cecil B.; Handfield, Robert B. (New Delhi : Pearson Edu, 2006)
Introduction to Operations and Supply Chain Management provides an integrated and comprehensive treatment of both operations and supply chain management.